ANTESEDEN LOYALITAS PENGGUNA PUSAT BAHASA UNIVERSITAS SUMATERA UTARA - Loebis, Roma Ayni A.; Gultom, Parapat (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Language services managed by the Language Center include TOEFL-ITP tests, ECT (English Competency Test) tests, English courses, Japanese courses, Arabic courses, Mandarin courses, and translation services for English, Japanese, Mandarin, and ethnic languages. This research aims to identify the factors (antecedents) that influence user loyalty to the Language Center at USU. The data analysis technique used is quantitative causal with multiple linear regression methods and partial least squares structural equation modeling (PLS-SEM). The population in this research consists of service users from April 2024, with a sample size of 110 respondents. The independent variables are tangibles, empathy, reliability, responsiveness, and assurance. The dependent variable is user loyalty, with the moderating variable being the availability of digital and non-digital facilities. The results indicate that service quality significantly influences user loyalty, while the availability of digital and non-digital facilities does not significantly affect user loyalty at the Language Center at USU. The implications of this research suggest that the Language Center at USU must maintain professionalism to sustain user loyalty.Keyword: Antecedents, Loyalty, Service Users